Pengaruh Tuntutan Pendidikan, Pemahaman Akuntansi dan Ukuran Usaha Terhadap Penyajian Laporan Keuangan Berdasarkan Sak Etap (Studi Empiris pada UMKM di Wilayah Kab. Brebes) - Ayusa Nitasari; Maftukhin; Andi Yulianto; Amelia Sholeha; Afti Sulastri (Universitas Muhadi Setiabudi, 2019)
Micro, Small and Medium Enterprises (MSMEs) are one of the factors driving the Indonesian economy. However, in reality, MSME players are still experiencing difficulties in the capital sector because they are constrained by the preparation of financial statements. This study aims to determine and analyze the influence of educational demands, understanding accounting and business size on the presentation of financial statements based on SAK ETAP on MSMEs in the Brebes Regency area. The sample of this study was 108 business actors consisting of small and medium enterprises located in three districts, namely Ketanggungan, Kersana and Banjarharjo Districts. Data collection in this study used questionnaires as research instruments. Test research instruments using validity and reliability tests. The hypothesis test uses a regression test preceded by a normality test, a multicollinearity test and a heteroskedasticity test. Furthermore, hypothesis testing is carried out using multiple regression tests. Keywords: Sales Volume, Operating Cost, Room Price and Net Income. The results showed that educational demands did not have a significant effect on the presentation of financial statements based on SAK ETAP, there was a positive influence on accounting understanding, and business size on the presentation of financial statements in accordance with SAK ETAP, there was a simultaneous influence of educational demand variables, understanding accounting and business size on the presentation of financial statements based on SAK ETAP.